2013
DOI: 10.1002/eji.201343335
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory stimuli induce galectin‐9 in human mesenchymal stromal cells to suppress T‐cell proliferation

Abstract: Human multipotent mesenchymal stromal cells (MSCs) are clinically applied to treat autoimmune diseases and graft-versus-host disease due to their immunomodulatory properties. Several molecules have been identified to mediate these effects, including constitutively expressed galectin-1. However, there are indications in the literature that MSCs exert enhanced immunosuppressive functions after interaction with an inflammatory environment. Therefore, we analyzed how inflammatory stimuli influence the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
90
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 41 publications
(82 reference statements)
5
90
0
Order By: Relevance
“…1A). From all markers included in our analysis, only Gal-9 mRNA showed a significant increase after IFN-g activation, as simultaneously demonstrated by Gieseke et al [30]. As described, we observed a minor increase by stimulation with TNF-a (Data not shown).…”
Section: Ifn-c and B Cells Enhance Gal-9 Expression In Mscssupporting
confidence: 86%
See 2 more Smart Citations
“…1A). From all markers included in our analysis, only Gal-9 mRNA showed a significant increase after IFN-g activation, as simultaneously demonstrated by Gieseke et al [30]. As described, we observed a minor increase by stimulation with TNF-a (Data not shown).…”
Section: Ifn-c and B Cells Enhance Gal-9 Expression In Mscssupporting
confidence: 86%
“…Shortly after, the role of galectin-3 was analyzed for its potential to suppress PBMC proliferation upon TLR activation [18]. Coinciding with our observations Gieseke et al demonstrated the inducebility of Gal-9 in MSCs by pro-inflammatory stimuli [30] and delivered a possible explanation how MSCs might improve tissue regeneration and influence inflammatory tissue environment after transplantation [34]. Here, we confirmed these results for pooled MSC populations and added B cells as a new target to the immune modulation with Gal-9.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Within the immune system, galectins are expressed by virtually all immune cells, either constitutively or in an inducible fashion [46]. Also, they can be expressed by a spectrum of normal and tumor cells.…”
Section: Galectins (Gal)mentioning
confidence: 99%
“…Gal-9 can be induced by IFN-γ and interleukin-beta (IL-1β) in various cell types and thus is upregulated in inflamed tissues. Gal-9 must be released by cells to exert its immunoregulatory properties [46].…”
Section: Galectins (Gal)mentioning
confidence: 99%